Statistical abstract of the United States 1969 - United States. Bureau of the Census; U.S. Census Bureau (Washington, DC : U.S. Dept. of Commerce, Economics and Statistics Administration, 1969)
A statistical reference and guide to over 250 statistical publications and sources from government and private organizations.
Description based on: 1995; title from print record.
Latest issue consulted: 2009 (viewed Apr. 15, 2009).
Vol. for 2004/2005 issued in a combined form.
Mode of access: Internet from the Census Bureau web site. Addresses as of 4/15/09: http://www.census.gov/compendia/statab/ (current ed.) and http://www.census.gov/compendia/statab/past%5Fyears.html (archived eds.) ; current access is available via PURLs.
Vols. for 1995-1997 issued by: Bureau of the Census; 1998- by: U.S. Census Bureau.
Has numerous supplements; beginning in 1993, data also available in CD-ROM publication with the same title.
Keywords: United States -- Statistics -- Periodicals; v